The Alternative Model of Personality Disorders (AMPD) from the Perspective of the Five-Factor Model - Widiger, Thomas A; McCabe, Gillian A (Psychopathology, 2020)
The fifth edition of the American Psychiatric Association's (APA) Diagnostic and Statistical Manual of Mental Disorders(DSM-5; American Psychiatric Association. Diagnostic and Statistical Manual of Mental Disorders. 5th ed. Washington: American Psychiatric Association; 2013) includes an Alternative Model of Personality Disorders (AMPD). The AMPD includes two components: the Criterion A level of personality functioning (i.e., impairments or deficits in the sense of self and interpersonal relatedness) and the Criterion B five-domain maladaptive trait model. The purpose of the current paper is to discuss the AMPD from the perspective of the Five-Factor Model (FFM) of general personality structure. The conclusion of this review is that both the Criterion A self-other deficits and the Criterion B traits can be understood as maladaptive variants of the FFM.The fifth edition of the American Psychiatric Association's (APA) Diagnostic and Statistical Manual of Mental Disorders(DSM-5; American Psychiatric Association. Diagnostic and Statistical Manual of Mental Disorders. 5th ed. Washington: American Psychiatric Association; 2013) includes an Alternative Model of Personality Disorders (AMPD). The AMPD includes two components: the Criterion A level of personality functioning (i.e., impairments or deficits in the sense of self and interpersonal relatedness) and the Criterion B five-domain maladaptive trait model. The purpose of the current paper is to discuss the AMPD from the perspective of the Five-Factor Model (FFM) of general personality structure. The conclusion of this review is that both the Criterion A self-other deficits and the Criterion B traits can be understood as maladaptive variants of the FFM.